NEW LATE HAUTERIVIAN TEREBRATULIDS FROM THE SOUTHWESTERN CRIMEA - Smirnova T.N. (My University, 2001)
The taxonomic composition of Late Hauterivian Terebratulidae of the Southwestern Crimea is reviewed. Two new genera, Middlemissithyris and Eichwaldithyris, are established, and six new species-Middlemissithyris rarus, Iberithyris oweni, I. variabilis, Eichwaldithyris rasilis, E. argutus, and Cyrththyris dagysi-are described.
Keywords: Hauterivian; Terebratulidae; Southwestern Crimea; Мезозой::Меловая::Нижний::Готеривский; Mesozoic::Cretaceous::Lower::Hauterivian